2017
DOI: 10.1007/s12519-016-0083-1
|View full text |Cite
|
Sign up to set email alerts
|

Clinical experience in the treatment of children who swallowed multiple magnetic foreign bodies: A report of five cases

Abstract: If magnetic foreign bodies cannot be removed by endoscopy, an operation is suggested as soon as possible to avoid serious complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…In this case, the two roots of the genus Artemisia remained in the body for more than 2 years [3][4] , and the edge of the patient with a length of about 14 cm, and a shorter one was about 7 cm. Among them, the right lung foreign body is easy to cause right pneumothorax, lung tissue compression.…”
Section: Discussionmentioning
confidence: 80%
“…In this case, the two roots of the genus Artemisia remained in the body for more than 2 years [3][4] , and the edge of the patient with a length of about 14 cm, and a shorter one was about 7 cm. Among them, the right lung foreign body is easy to cause right pneumothorax, lung tissue compression.…”
Section: Discussionmentioning
confidence: 80%
“…If not spontaneous passed, endoscopic and surgical procedures are the main treatment methods for gastrointestinal FBs. [7] Endoscopic treatment is preferred, as it is less traumatic, safe, has a high success rate, and associated with few complications. [8] In the present cases, the 2 patients swallowed multiple magnets that stuck together, making them a special type of FB ingestion.…”
Section: Discussionmentioning
confidence: 99%
“…4 Chung et al described a similar case in an adolescent with ASD who presented with a febrile urinary tract infection following an estimated 3-month diagnostic delay. 4 In addition to risks associated with the prolonged presence of any FB in the urinary system, reports of bowel erosion following ingestion of rare-earth magnets 12 raises concern for the possibility of similar bladder erosion if not promptly removed. Given the potential morbidity associated with delayed recognition, a low threshold of suspicion may help clinicians properly diagnose and treat patients with unexplained urinary symptoms in a timely fashion.…”
Section: Discussionmentioning
confidence: 99%
“…1,8 Intranasal insertion and oral ingestion occur most often, with the latter warranting emergent management to prevent bowel wall ischemia, necrosis, and possible perforation due to magnetic attraction. 1,12 Urethral insertion of the magnets is less common, and a PubMed English literature review identified only 4 prior pediatric cases, all in adolescent boys (Table 1). [2][3][4][5] Recognition and management of rare-earth magnets as FBs in a child's urinary system requires unique considerations, as illustrated by the diagnostic dilemma in our first case and the barriers to endoscopic removal in both cases.…”
Section: Discussionmentioning
confidence: 99%